1995
DOI: 10.1007/bf02761889
|View full text |Cite
|
Sign up to set email alerts
|

Empty sella in short children with and without hypothalamic-pituitary abnormalities

Abstract: A study was conducted on growth hormone (GH) response to oral clonidine (0.15 mg/m2), GH and cortisol responses to i.m. glucagon (0.1 mg/kg), and glucose response to an oral load of glucose (1.75 g/kg). Measurements were made on the circulating concentrations of free thyroxine (FT4), thyroid stimulating hormone (TSH) and different growth parameters and CT sellar images in 25 GH deficient children (Peak GH response to clonidine and glucagon < 7 ug/ml), 15 growth retarded children (Ht < 5th percentile for age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
5

Year Published

1996
1996
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
0
10
0
5
Order By: Relevance
“…The most frequent cause of the endocrinological dysfunction is the primary pituitary dysfunction. Several studies have reported primary empty sella in children with hypopituitarism due to the hypothalamic insufficiency [7,8], however; only one case of empty sella syndrome with hypothalamic hypopituitarism in adulthood has been reported as far as we have searched [9]. Here we present a case of panhypopituitarism with empty sella syndrome in which hypothalamic dysfunction was strongly speculated with a review of the literature.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The most frequent cause of the endocrinological dysfunction is the primary pituitary dysfunction. Several studies have reported primary empty sella in children with hypopituitarism due to the hypothalamic insufficiency [7,8], however; only one case of empty sella syndrome with hypothalamic hypopituitarism in adulthood has been reported as far as we have searched [9]. Here we present a case of panhypopituitarism with empty sella syndrome in which hypothalamic dysfunction was strongly speculated with a review of the literature.…”
mentioning
confidence: 86%
“…Taken together, it is strongly suggested that the panhypopituitarism is caused by hypothalamic dysfunction. Although, several studies have reported hypothalamic insufficiency with empty sella in children [7,14], it is extremely rare in adulthood [9]. In children, congenital deficiency or structural anomaly in the hypothalamus has been suggested as a cause [15,16].…”
Section: Case Reportmentioning
confidence: 99%
“…Las escasas publicaciones que existen al respecto 4,17,22,89,98,106,111 , ponen de manifiesto que no suelen presentar el síndrome típico de STVP de los adultos 111 , ni una mayor prevalencia femenina.…”
Section: Stvp En Los Niñosunclassified
“…También es frecuente que se asocie a otras enfermedades congénitas, como la anemia de células falciformes cuando se asocia a déficit de HG (100% de los casos de Soliman 89 ) o al síndrome del carcinoma de células basales nevoides (60% en la serie de Takanashi 98 ), así como a otras anomalías de la base de cráneo, como la displasia ósea del esfenoides. Es decir, la STV en niños no suele tener el carácter benigno propio de los adultos.…”
Section: Stvp En Los Niñosunclassified
See 1 more Smart Citation